TI_GERICHTE 32.2020.5 vom 26. November 2019 , Assegno grandi invalidi (AGI) per minorenni e supplemento per cure intensive (SCI) - TI Tribunale d'appello (2019)
Assegno grandi invalidi (AGI) per minorenni e supplemento per cure intensive (SCI)